Dukungan Ekologi Berbasis Perkembangan Sosial untuk Meningkatkan Kemampuan Keterampilan Sosial Anak - Maharani, Laila (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2017)
Social skills in children are the basis for living with others. Therefore, a model of social-based ecological support is needed to improve the social skills of children. With the developmental ecology, the various potentials that exist in children can be facilitated, because the child's developmental ecology is the whole environment that allows children to get the facilities and the right stimulus, so that there is a healthy learning process. The research was conducted at TK Ar Rahman Bandar Lampung, in July-December 2017. The target of this research is the students of group B TK Ar Rahman as the main object of research and teacher as secondary object or model user. this study the authors only limit in the first stage of the preliminary study in the form of analysis of the next needs to be done further research by developing learning model.